História em quadrinhos: uma alternativa didática para o ensino e aprendizagem de doenças causadas por helmintos - Belém, Josiana Ferreira (2023)
Helminthiases are intestinal diseases caused by helminths (worms), representing a significant challenge for public health. This problem is aggravated by the disparity in the distribution of basic sanitation services and the lack of information about infections, their modes of transmission and prophylactic measures. Thus, one of the ways to promote health and encourage healthy lifestyle practices is through health education in the school environment. This practice not only encourages changes in behavior, but also contributes substantially to improving quality of life and fosters the development of knowledge that promotes self-care. In this learning context, the use of comic books can be presented as a didactic alternative that facilitates the teaching and learning process on the topic of helminthiasis. Comics and their various genres have become popular in recent decades and have been inserted into the school environment with the purpose of assisting in the development of learning situations. Therefore, this research aims to investigate a didactic proposal systematized in the Three Pedagogical Moments (3MP), focusing on teaching and learning the theme of helminthiasis through comic books, aimed at high school students. The approach adopted in this research is qualitative in nature, using participatory research as its methodology. Data collection took place through the application of a diagnostic questionnaire, the answers to which helped both in verifying prior knowledge about the topic in question and in characterizing the subjects; and final questionnaire for the research and production of digital comics, in addition to participant observation. The results of the questionnaires were tabulated and analyzed in Microsoft Excel and presented in the form of tables and graphs, while the comics were evaluated based on an analytical rubric. The educational product resulting from this research is a teaching guide entitled “Health education from the production of comic books: teaching guide”, which presents a didactic proposal for health education in high school. The use of 3MP in conjunction with the language of comics, combined with activities centered on the active participation of students, played a fundamental role in the engagement and motivation of participants throughout the pedagogical activities. This resulted in a better understanding of the content studied and the acquisition of new knowledge related to the forms of transmission, symptoms, causative agents and prevention measures for helminthiasis.